A MANAJEMEN DIABETES MELITUS DALAM KEHAMILAN: MANAJEMEN DIABETES MELITUS DALAM KEHAMILAN - ADITYA NUGRAHA (Yayasan Pendidikan Medika Indonesia, 2023)
Diabetes mellitus (DM) is currently a disease that epidemiologically shows a tendency to increase in incidence and prevalence in various parts of the world, including Indonesia. Diabetes mellitus in pregnancy is divided into two groups, namely DM that was previously known and later became pregnant (pregestational DM) and DM that was newly discovered during pregnancy (GDM). Diabetes mellitus in pregnancy is a public health problem because this disease has a direct impact on the health of the mother and fetus. This disease is one of the most common medical complications during pregnancy, with an incidence of 3-5% of all pregnancies. Uncontrolled diabetes during pregnancy results in an increased risk of miscarriage in the first trimester, congenital abnormalities of the fetus, especially heart and central nervous system disorders, increased fetal death, premature labor, preeclampsia, ketoacidosis, polyhydramnios, macrosomia, birth trauma, delayed lung maturation, respiratory distress syndrome. , jaundice, hypoglycemia, and increased perinatal mortality. Therefore, a comprehensive treatment is needed in dealing with gestational diabetes.